Penerapan Pembelajaran Pendidikan Agama Islam Terhadap Anak Berkebutuhan Khusus Di Sekolah Luar Biasa - Rinaldho Rinaldho; Robi Agus Pratama; Novrian Ramadhan; Wismanto Wismanto; Nuradillah Nuradillah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Inclusive education is about the equal rights that every child has. Inclusive education is a process of removing barriers that separate students with special needs from normal students so that they can learn and work together effectively in one school. This research aims to determine PAI learning management in inclusive schools. In this research the author analyzed the data using qualitative analysis techniques. The method used in this research is qualitative research based on research libraries (library research). There are four results from this research, among others (1) planning PAI learning for ABK in an inclusion setting (2) implementing PAI learning with various strategies (3) Evaluation of PAI learning results (4) Obstacles faced in planning, implementing and evaluating PAI learning in inclusive schools.